Physical and mechanical characterization of polyurethane foam core of sandwich panels of various densities - Benzo, Pier Giovanni (2022)
Sandwich foaming is a manufacturing process in which a liquid monomer mixture is injected on the bottom face sheet of the sandwich panel where it polymerizes to form cross-linked polyurethane (PUR) foam providing an adhesive joint between the bottom and upper metal sheets. The single-step process avoids manual operations in the assemblage of the panel and the use of adhesive. However, the PUR foam in the core of the panel and at foam-to-face sheet interface may present fluctuations in the mechanical properties. The aim of this study is the mechanical and thermophysical characterization of PUR foam of various densities produced by sandwich foaming. Additionally, a qualitative assessment of the foam-to-face sheet interface is carried out based on the results of the flatwise tensile and shear tests.